2022
DOI: 10.1001/jamaoto.2022.0082
|View full text |Cite
|
Sign up to set email alerts
|

Manual Therapy for Patients With Radiation-Associated Trismus After Head and Neck Cancer

Abstract: IMPORTANCETrismus is highly prevalent in head and neck cancer (HNC) survivorship. Current standards for trismus treatment include various stretch-based exercise protocols as a primary and single treatment modality with limited evidence regarding the role of manual therapy (MT) for this indication.OBJECTIVE To assess the effect size and associations of response to MT to increase oral opening in the setting of radiation-associated trismus. DESIGN, SETTING, AND PARTICIPANTS This retrospective case series was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…The comprehensive management of trismus within the context of head and neck cancer patients necessitates a multidisciplinary strategy that encompasses the expertise of radiation oncologists, oncology nurses, speech therapists, physiotherapists, and dentists. Physical interventions, such as active and passive jaw exercises, manual stretching, and myofascial release techniques, are employed to ameliorate restricted mouth opening and mitigate fibrotic tissue formation [ 86 ]. The implementation of pharmacological agents, encompassing muscle relaxants and anti-inflammatory medications, may alleviate muscular discomfort in some cases and decrease muscular rigidity.…”
Section: Trismusmentioning
confidence: 99%
“…The comprehensive management of trismus within the context of head and neck cancer patients necessitates a multidisciplinary strategy that encompasses the expertise of radiation oncologists, oncology nurses, speech therapists, physiotherapists, and dentists. Physical interventions, such as active and passive jaw exercises, manual stretching, and myofascial release techniques, are employed to ameliorate restricted mouth opening and mitigate fibrotic tissue formation [ 86 ]. The implementation of pharmacological agents, encompassing muscle relaxants and anti-inflammatory medications, may alleviate muscular discomfort in some cases and decrease muscular rigidity.…”
Section: Trismusmentioning
confidence: 99%
“…5,13 Patients with pre-existing compromised dentition or temporomandibular joint disorders are at greatest risk of developing trismus following cancer treatment. 10,14,15 Trismus has been treated using a range of jaw-stretching devices, 16,17 however, they are under-utilized due to factors such as cost, portability, and safety in the setting of compromised bone and dentition. 18 Restorabite™ is a new device which is portable and delivers regulated, measurable, and individualized incremental forces.…”
Section: Introductionmentioning
confidence: 99%
“…Trismus has been treated using a range of jaw‐stretching devices, 16,17 however, they are under‐utilized due to factors such as cost, portability, and safety in the setting of compromised bone and dentition 18 . Restorabite™ is a new device which is portable and delivers regulated, measurable, and individualized incremental forces.…”
Section: Introductionmentioning
confidence: 99%
“… 35 , 36 One study found that MT may be considered for frontline or adjuvant treatment of radiation-associated trismus by demonstrating significant improvement in maximum interincisal opening for HNC patients with post-treatment trismus. 37 Furthermore, the addition of MT to a cervical exercise program has shown statistically significant improvement in chronic neck pain patients in both the short and mid-term. 38 …”
Section: Introductionmentioning
confidence: 99%